Faktor - Faktor yang Mempengaruhi Pengangguran Terbuka di Provinsi Jawa Tengah Tahun 2009-2014 - Yunani Tiya Kasanah; Anifatul Hanim; P. Edi Suswandi (UPT Penerbitan Universitas Jember, 2018)
Economic development of a country aims to increase social welfare by expanding employment opportunities and direct distribution of income evenly. Uneven economic development would be problematic one of them is unemployment. Unemployment is a complex problem that can lead to social phenomena in society as someone who did not work so it does not earn. It is therefore necessary to find a solution to overcome the problem of unemployment. This study aims to determine the effect of the minimum wage, the labor force and economic growth on unemployment in Central Java province in 2009-2014. The analytical method used in this research is panel data regression with fixed effect model approach (FEM). Based on the analysis, it is known that variable minimum wage a significant negative effect on the variable open unemployment in Central Java, a variable workforce positive and significant effect on the variable open unemployment in Central and variable economic growth does not significantly influence the variables of unemployment in Central Java. Keywords: Unemployment, Minimum Wages, Labor Force, economic growth